Critical Discourse Analysis of Jokowi Tweets Based on the ideational meta-function Systemic Functional Linguistic meta-function - Rahman Nur, Dedi; Widodo, Pratomo (Script Journal: Journal of Linguistics and English Teaching, 2022)
Background: Throughout order to analyze texts and discourses, Critical Discourse Analysis makes use of Systemic Functional Linguistics (SFL) as a tool. Through use of Systemic Functional Linguistics is particularly interesting to Critical Discourse Analysis, even though the other linguistic models are also useful in the field. This is due to the model's emphasis on language use, as well as its informative and social functions. Methodology: The qualitative approach was utilized by the researcher since it is suitable with research by analyzing visual text or text that is visible and legible or it can be used to investigate the structure of words or visual text as language. Findings: The findings from the Principal Component Analysis (PCA) on the transitivity of Twitter texts related to Indonesia President Joko Widodo reveal interesting patterns. Focusing on the first fifteen Twitter posts in December, the analysis of the initial post highlighted four instances of Material Processes with the goal of improving farmers' productivity in Trenggalek. The subsequent posts showcased diverse transitivity patterns, covering themes such as economic development, government openness to criticism, responses to global events like the Omicron variant, and a commitment to environmental sustainability. Common elements across the posts included economic initiatives outside Java, infrastructure development, and social welfare efforts. Overall, these Twitter posts depicted President Joko Widodo's engagement with various issues, employing a mix of informative, persuasive, and directive communication styles. The analysis provides valuable insights into the President's priorities and governance approach during this period, offering a nuanced understanding of the multifaceted nature of his communication. Conclusion: The research provides valuable insights into the linguistic strategies employed by President Joko Widodo in his Twitter communication, shedding light on how the transitivity system is utilized to convey messages and shape perceptions